2019
DOI: 10.33263/lianbs83.571575
|View full text |Cite
|
Sign up to set email alerts
|

Co-valorization of agro-industry by-products: effect of citrus oil on the quality of soap derived from palm fatty acid distillate and spent bleaching clay

Abstract: This study deals with the co-valorization of spent bleaching clay (SBC) and palm fatty acid distillate (PFAD) –by-products of palm oil refining plants- through soap manufacture. Obtained SBC and PFAD samples show differing acidity and saponification values depending on fatty acids and acylglycerols content. Soaps are prepared using the stoichiometric amount of NaOH, under the varying proportion of water introduced through the basic solution. The mixing SBC and PFAD (ratio 1:3), the reaction completion (92.5%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Peroxide values of palm stearin, rice bran oil, and soybean oil were lower than that of the oil mixture. This shows the governing effect of oxidation on fatty acids, wellknown to affect the physicochemical properties on refining and mixing oils (Punvichai & Pioch, 2019a, 2019b. Fatty acid compositions of the samples are given in Table 3.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Peroxide values of palm stearin, rice bran oil, and soybean oil were lower than that of the oil mixture. This shows the governing effect of oxidation on fatty acids, wellknown to affect the physicochemical properties on refining and mixing oils (Punvichai & Pioch, 2019a, 2019b. Fatty acid compositions of the samples are given in Table 3.…”
Section: Resultsmentioning
confidence: 91%
“…The analysed fatty acid compositions of the oils in this study are shown in Table 3. Palm stearin shows larger proportions of saturated and monounsaturated fatty acids (64.81% and 29.66%, respectively) than of polyunsaturated fatty acids (Punvichai & Pioch, 2019a, 2019b). But, palm stearin contains less MUFA (29.66%) than rice bran oil (41.82%).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The overproduction of some foods, such as tangerines, brings unpleasant effects on health and the environment, especially in the areas surrounding municipal landfills. Therefore, finding some alternatives to recover these crop wastes is necessary [45][46][47]. In the case of mandarin, it might be convenient to find economically feasible ways to use the tangerine peel to produce essential oils with high contents of bioactive substances such as d-limonene [48].…”
Section: Introductionmentioning
confidence: 99%